(untitled) (Cadernos de Filosofia Alemã: Crítica e Modernidade, 2008)
In Ueber Wahrheit und Luege in aussermoralischen Sinne one finds a discussion between two notions, each of them pointing out to a specific attitude regarding language: truth drive and artistic drive. This paper takes into account these two conceptions with the intention of specifying what notion of truth is at stake in the Nietzschean critique carried out in this text.